PEMBARUAN HUKUM PIDANA KORUPSI PASCA REVISI UU NOMOR 1 TAHUN 2025 ANALISIS YURIDIS ATAS PERLINDUNGAN PEJABAT BUMN DAN IMPLIKASINYA TERHADAP EFEKTIVITAS PENEGAKAN HUKUM - Opik Sepriadi; Siti Humulhaer; Salman Al Ghifari; Unggul Budi (CV. Lafadz Jaya, 2026)
The amendment to Law No. 1 of 2025 amending Law No. 31 of 1999 on the Eradication of Corruption Offences (the Anti-Corruption Law) introduces new dynamics into Indonesia’s criminal law system regarding corruption, particularly in relation to the management of State-Owned Enterprises (SOEs). This study aims to conduct a legal analysis of the updates to corruption criminal law following the amendment of Law No. 1 of 2025, focusing on the protection of SOE officials and its implications for the effectiveness of law enforcement. Using a normative legal research method with a legislative and conceptual analysis approach, this study found that the revision of Law No. 1 of 2025 introduced a distinction between legitimate business risks and corrupt acts through the strengthening of the business judgment rule and the removal of the status of public officials for SOE officials (Article 9G). Although this amendment provides legal certainty and protection against the criminalisation of business policies that are not malicious in nature, there is a risk of moral hazard and a weakening of the authority of the Corruption Eradication Commission (KPK). This study recommends the need for regulatory harmonisation among law enforcement agencies, the strengthening of internal oversight systems within SOEs, and a re-evaluation of Article 9G to maintain a balance between legal protection and the eradication of corruption.